Classroom acoustic conditions and primary school children's behaviour: A scoping review. Issue 4 (December 2022) - Mealings, Kiri
The aim of this scoping review was to determine what is known from the literature about the effect of different classroom acoustic conditions on different primary school children's behaviour. A scoping review using the PRISMA-ScR protocol was conducted in March 2022. ERIC, PubMed, Scopus and Web of Science databases were searched using the search term classroom AND (acoustic* OR noise OR reverb*) AND (behav* OR motivat* OR attitude OR persist* OR flexib* OR engage* OR interpersonal). In all, 14 articles were relevant. The populations studied included children who were typically developing, had autism spectrum disorder, attention deficit hyperactivity disorder or were deaf or hard of hearing. Several behaviours including learning, externalising and internalising behaviours were investigated. The results suggested that poor classroom acoustic conditions can negatively impact children's behaviour. However, due to heterogeneity of the methodologies used in this small number of studies, future research is proposed to better understand the relationship.